The impact of market drops is different for investors before and after retirement - Samsa, Greg (Archives of Business Research, 2020)
As applied to investing for and during retirement, the popular financial press has promulgated two memes about the impact of market drops: (1) for those investing for retirement market drops aren’t problematic; and (2) for those in retirement market drops are. We use simulation to illustrate the logic behind these memes, to demonstrate that they are mostly but not entirely true, and finally to restate them more precisely. Although sequence of returns risk is not present during the accumulation phase as an investor plans for retirement, it can have a significant (and perhaps underestimated) impact during retirement. This, however, can place the retiree in a predicament – namely, settle for lower returns and lower distributions during retirement or gamble on stocks. However, it does not necessarily imply that retirees must abandon the expected returns associated with stocks, because of the ability to write deep-in-the-money covered call options, which harvest the expected market return (but no more than this) with limited variability.